ANALISIS TINGKAT KEPUASAN PELAYANAN PENUMPANG PELABUHAN KAMAL JAWA TIMUR - Kusmaryati Kusmaryati; Nurani Hartatik (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
Kamal-Madura Port is an ASDP (River, Lake and Ferry Transport) ferry port in Bangkalan-Madura Regency, the operation of the Suramadu Bridge has an impact on the performance of the Kamal-Madura Port, one of which is a decrease in the vitality of the area such as damaged road conditions, several canteens that have not been operating for a long time. With the decrease in ferry activities at the Kamal-Madura Port, there has also been a decrease in the activities of traders, small industries and public transportation. As a company that offers transportation services, Kamal-Madura Port must have good service quality so that it can continue to grow, by measuring the level of satisfaction or passenger perceptions of service quality it is very useful for port managers or administrators to find out which components need to be improved and quality improved. Researchers use the IPA method (Importance Perfomance Analysis), This method serves to measure the level of service quality in a company and which priorities must be maintained so that the company's performance is in line with consumer expectations. The results of this studyThe results of the study show that the mean value of respondents' satisfaction answers is 51.52% which can be concluded that the level of passenger satisfaction at Kamal-Madura Port is average, namely between satisfied and dissatisfied with port facility services because the percentage is <60%.